The multifaceted role of macrophages during acute liver injury - Hassan, Ghada S.; Flores Molina, Manuel; Shoukry, Naglaa H. (Frontiers in Immunology, 2023)
The liver is situated at the interface of the gut and circulation where it acts as a filter for blood-borne and gut-derived microbes and biological molecules, promoting tolerance of non-invasive antigens while driving immune responses against pathogenic ones. Liver resident immune cells such as Kupffer cells (KCs), a subset of macrophages, maintain homeostasis under physiological conditions. However, upon liver injury, these cells and others recruited from circulation participate in the response to injury and the repair of tissue damage. Such response is thus spatially and temporally regulated and implicates interconnected cells of immune and non-immune nature. This review will describe the hepatic immune environment during acute liver injury and the subsequent wound healing process. In its early stages, the wound healing immune response involves a necroinflammatory process characterized by partial depletion of resident KCs and lymphocytes and a significant infiltration of myeloid cells including monocyte-derived macrophages (MoMFs) complemented by a wave of pro-inflammatory mediators. The subsequent repair stage includes restoring KCs, initiating angiogenesis, renewing extracellular matrix and enhancing proliferation/activation of resident parenchymal and mesenchymal cells. This review will focus on the multifaceted role of hepatic macrophages, including KCs and MoMFs, their spatial distribution and roles during acute liver injury.